Development of Entrepreneurial Orientation through Specific Critical Incident (SCI) Entrepreneurial Learning on Business Performance (Case Study of Culinary Small and Medium Enterprises (SMEs) in South Kalimantan Province) - Fitriyadi, Fitriyadi; Larasati, Endang; Djastuti, Indi; Nugraha, Hari Susanta; Prabawani, Bulan; Yuwanto, Yuwanto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This research aims to reveal the Development of Entrepreneurial Orientation through Specific Critical Incident (SCI) Entrepreneurial Learning on Business Performance. This study use qualitative research design. The result shows that effect of entrepreneurial orientation on specific critical incident (SCI) entrepreneurial learning has a p-value of 0.002 where the value is less than 0.1 (0.002 < 0.1), so it can be concluded that hypothesis 1 of this study is acceptable or there is an influence of entrepreneurial orientation on specific critical incident (SCI) entrepreneurial learning at a real level of 10% with a parameter coefficient value of 0.466. This means that better entrepreneurial orientation is able to increase specific critical incidents of entrepreneurial learning in entrepreneurship for culinary business actors in South Kalimantan.